Size-Dependent Switching Properties of Spin-Orbit Torque MRAM With Manufacturing-Friendly 8-Inch Wafer-Level Uniformity - Sk Ziaur Rahaman (IEEE, 2020)
We have developed a manufacturing-friendly spin-orbit torque magnetic random access memory (SOT-MRAM) technology in CMOS compatible 8-inch fab process. The proposed SOT-MRAM process technology resolves etching non-uniformity and reduction of high resistivity heavy-metal nanowire resistance issues. Besides, we present device size-dependent switching current threshold in the proposed SOT-MRAM cell structure. To realize the potential of our fabricated SOT-MRAM, wafer-level uniformity, cycling and temperature dependence SOT switching have been comprehensively investigated. Furthermore, the thermal stability factor ( ${Δ }$ ) was calculated from temperature-dependence SOT switching to fulfill the thermal stability criteria, i.e., > 10 years of this emerging SOT-MRAM technology.